Argumentation in Multi-Agent Systems 8th International Workshop, ArgMAS 2011, Taipei, Taiwan, May 3, 2011, Revised Selected Papers - McBurney, Peter; Parsons, Simon; Rahwan, Iyad.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly reviewed post-proceedings of the 8th International Workshop on Argumentation in Multi-Agent Systems, ArgMas 2011, held in Taipei, Taiwan in May 2011 in association with the 10th International Conference on Autonomous Agents and Multi-Agent Systems (AAMAS 2011). The 8 revised full papers taken from ArgMAS 2011. Also included are 5 invited papers based on presentations on argumentation at the AAMAS 2011 main conference. All together the 13 papers included in the book give a representative overview on current research on argumentation in multi-agent systems. The papers are listed alphabetically by first author within three thematic topics: foundations and theory; argumentation and dialogue; and applications.
Keywords: Computer science; Computer Communication Networks; Information storage and retrieval systems; Artificial intelligence; Computer vision; Computer Science; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Computer Communication Networks; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Computer Imaging, Vision, Pattern Recognition and Graphics